Light - Llewellyn, Claire; Moller, Ray (Mankato, Minn. : Sea-to-Sea, 2005)
Discusses different types of light, including sunlight, electric light, and firelight, shows what happens when the sun's light is blocked, and looks at the uses of light.
Includes index.
1.4
K-3
Keywords: Light -- Juvenile literature; Light; Light; Light